Structure matching mechanism of nRu/FeCo2O4 for highly-selective oxidation of HMF toward FDCA - Wang, Qiong-Yu (2025)
The selective oxidation of 5-hydroxymethylfurfural (HMF) toward 2,5-furandicarboxylic acid (FDCA) offers a promising green pathway to obtain monomers for the synthesis of biodegradable plastics. However, developing a high-selectivity catalyst and understanding the catalytic mechanism are still great challenge. Here, we synthesize a nRu/FeCo2O4 catalyst with Ru nanoparticles loaded on FeCo2O4. The nRu/FeCo2O4 presents excellent HMF oxidation activity with 100% HMF conversion efficiency and 99% FDCA yield under optimized conditions. Density-functional theory calculations further reveal the structure matching mechanism of nRu/FeCo2O4 for high-selective oxidation of HMF toward FDCA, that is, Ru loading in FeCo2O4 provides a more suitable structure matching configuration for adsorption of two-side chains in HMF, which could optimize the adsorption energy and thus increase reactivity. In short, this work provides a promising structure matching strategy for designing dual-active-site relay catalyst to oxidize -CHO and C-OH groups in HMF and thus achieve highly-selective oxidation of HMF toward FDCA.